Exploring Students’ Reading Enthusiasm Toward Multimodal Digital Texts: Evidence from Interactive Reading Instruction - Sri Wiyanah; Adelia Dwi Hardiyati; Nafisah Endahati (Journal of English Language Teaching and English Linguistics, 2026)
Interactive media, such as animation, video, and learning applications, offer a more dynamic learning experience and can stimulate student interest. However, there are still limitations in understanding the extent to which interactive media can play a role in learning, especially reading. This study aims to determine the level of student enthusiasm in learning to read using interactive media MDT (Multimodal Digital Text). The method used quantitative descriptive. Questionnaires, observation, and interview were used to gather data. The results show that students have moderate level of enthusiasm for reading through interactive technology. The results of the study showed that students' enthusiasm was at a medium level with observation results 80% of student interaction with interactive media, 67% of student responses used interactive media, 78% of students' enthusiasm in reading using interactive media and questionnaires of 72.8%, as well as interview results showing that students were quite enthusiastic about reading using interactive media. Students have sufficient interest in reading using interactive media and show enthusiasm when reading. These results suggest that interactive media can support students’ reading engagement and interest. Based on these results, it is recommended that educators integrate more interesting reading media for learning, so that the level of enthusiasm and interest in reading for students is high. Keywords: Digital Text; Enthusiasm; Interactive Media; Reading